Blue Carbon Regulations and Implementation in Several Countries: Lessons for Indonesia - Zaid, M; Ricky, Ricky; M H Sedera , Rakotoarisoa (Journal of Law, Environmental and Justice, 2025)
This research seeks to examine novel concepts in global carbon emission reduction initiatives. According to several kinds of literature, the mitigation of carbon emissions can be achieved through the Blue Carbon Ecosystem (EKB) idea.  EKB is a concept that enhances aquatic regions to sequester carbon emissions.  EKB aims to mitigate carbon emissions and positively influences the national economy, particularly benefiting coastal areas.  This study employs a normative legal research methodology utilizing a conceptual, legislative, and comparative law approach. Research findings indicate that Indonesia has established regulations regarding blue carbon in Presidential Regulation 98 of 2021 pertaining to Carbon Economic Value.  Nonetheless, the existing regulation has inadequately facilitated the implementation of blue carbon in Indonesia. The findings indicate that 1) The blue carbon concept in Indonesia presents a significant opportunity to mitigate emissions and serve as an economic resource through the Carbon Economic Value scheme; 2) Various countries have successfully implemented blue carbon initiatives to harmonize environmental and economic considerations, emphasizing legal protection, institutional frameworks, and community engagement; 3) The regulatory framework for blue carbon in Indonesia exhibits several deficiencies, including a lack of regulatory coherence, overlapping authorities, insufficient community involvement, and an absence of equitable benefit distribution